Kelayakan Kulit Salak Dalam Pembuatan Nail Art Sebagai Penunjang Tampilan Rias Fantasi - Sofia Daniati; Lola Aulia; Widiati Alifah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
One type of fruit that is liked by people in Southeast Asia, namely Salak. The development of nail art has become one of the supporting appearances for women. So that it becomes a source of ideas in new innovations in the world of nail art. The purpose of this study was to find out how to make nail art by utilizing zalacca peels. In this study using the method, observation, documentation, literature and experimental methods Utilization of zalacca skin in making nail art through three stages, namely preparation of material tools and manufacturing steps. The results of the feasibility test from the five validators, namely the color assessment indicator score 23 is said to be very feasible, the form score 23 is said to be very feasible, the neatness score is 21 is said to be very feasible, and the design gets a score of 23 which is said to be very feasible so that it can be concluded that the product is said to be very feasible. .5% nail art color involved suitable for women's skin, 98.8% beauty nail art color gradations, 96.3% beauty nail art accessories, 98.8% accessories for fantasy makeup, 61.3% nail art accessories in fashion, 86.3% zalacca nail art accessories not excessive, 96.3% accessories on nail art to match, 96.3% nail art able to compete and 98.8% nail art being one of the innovations based on the results of the test 87% of respondents said they liked snake fruit nail art products